Prognostic impact of changes in left ventricular ejection fraction and wall motion score index in patients with myocardial infarction - Bae, Min-Wook; Moon, Seong-guen; Jung, Kyung-Tae; Kim, Won-Ho; Park, Sang-Hyun; Ahn, Jihun; Hwang, Jin-Yong; Oh, Seok Kyu; Hur, Seung Ho; Jung, Myung Ho; Lee, Kyu-Sun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe prognostic significance of changes in left ventricular ejection fraction (LVEF) and wall motion score index (WMSI) in patients with myocardial infarction remains unclear.MethodsThis study evaluated whether changes in LVEF and WMSI can predict clinical outcomes and LV remodeling in post-AMI patients. Using data from the Korea Acute Myocardial Infarction Registry-National Institutes of Health (KAMIR-NIH), 3,510 AMI patients who underwent percutaneous coronary intervention (PCI) were retrospectively analyzed. LVEF and WMSI were assessed via echocardiography at baseline and one-year post-PCI. The primary outcome was major cardiovascular adverse events (MACE), a composite of all-cause death, recurrent myocardial infarction (MI), and rehospitalization for heart failure at three years.ResultsAmong 3,510 AMI patients, 1,561 (44.5%) showed improvement in both LVEF and WMSI at one year after PCI, 1,150 (32.8%) experienced improvement in either LVEF or WMSI, while 799 (22.8%) had deterioration in both. The incidence of MACE was significantly lower in patients with improvement in both LVEF and WMSI (7.8% vs. 12.5% vs. 17.1%, P < 0.001). These patients also exhibited the highest rate of LV reverse remodeling and the lowest rate of adverse remodeling. Both the random forest and logistic regression models identified changes in LVEF and WMSI as significant predictors of MACE and LV remodeling.ConclusionIn AMI patients, improvement in both LVEF and WMSI post-PCI was associated with a lower risk of MACE and a higher likelihood of LV reverse remodeling. These findings highlight the prognostic value of LVEF and WMSI changes in guiding long-term management strategies.